Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1155/2013/241485
|View full text |Cite
|
Sign up to set email alerts
|

Soft Rough Approximation Operators and Related Results

Abstract: Soft set theory is a newly emerging tool to deal with uncertain problems. Based on soft sets, soft rough approximation operators are introduced, and soft rough sets are defined by using soft rough approximation operators. Soft rough sets, which could provide a better approximation than rough sets do, can be seen as a generalized rough set model. This paper is devoted to investigating soft rough approximation operations and relationships among soft sets, soft rough sets, and topologies. We consider four pairs o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…Definition 2.4 [15] Let Ŝ = (F, A) be a soft set over Ŵ . Then the pair A Ŝ = Ŵ , Ŝ is called a soft approximation space, we define the soft A Ŝ-lower and soft A Ŝ-upper approximations of any subset M ⊆ Ŵ respectively by the following two operations:…”
Section: Soft Set Theory and Soft Rough Setmentioning
confidence: 99%
See 3 more Smart Citations
“…Definition 2.4 [15] Let Ŝ = (F, A) be a soft set over Ŵ . Then the pair A Ŝ = Ŵ , Ŝ is called a soft approximation space, we define the soft A Ŝ-lower and soft A Ŝ-upper approximations of any subset M ⊆ Ŵ respectively by the following two operations:…”
Section: Soft Set Theory and Soft Rough Setmentioning
confidence: 99%
“…etc. Researchers have implementing various kinds of soft, rough and fuzzy sets (see [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…To …nd approximation of a set, Shabir et al [43] proposed modi…ed soft rough sets. Li et al [26] investigated soft rough approximation operators and showed that Pawlak's rough set model are a special case of soft rough sets and every topological space on initial universe is a soft approximation spaces. Sun and Ma [44] proposed a new concept of soft fuzzy rough set by combining the fuzzy soft set with the traditional fuzzy rough set.…”
Section: Introductionmentioning
confidence: 99%